The Transformative Power of Environmental Education in the Consumption of Safety: The Case of a Popular Housing Estate - River Chávez Santos; Angelica María Carrasco Rituay; Jesús Rascón; Yuri Reina Marín; Einstein Sánchez Bardales; Ytmar Tatiana Chávez Santos; Rosas Carranza Guevara (Qubahan Academic Journal)
Water is a basic resource for the survival of human beings, however, not everyone has access to this resource. Therefore, this study aimed to evaluate the impact of an educational intervention in a popular urbanization that lacks access to drinking water and is supplied by surface wells. A pre-experimental quantitative methodology was used that involves three stages: diagnosis, educational intervention and evaluation. The results showed that the educational intervention had significant changes in knowledge and water safety consumption habits (p < 0.001), furthermore learning persisted after the educational intervention and habits continued to improve; also, it was identified that there were no significant differences in gender and educational level. It is concluded that implementing short-term environmental education programs contributes to bringing about change in vulnerable populations that do not have access to safe drinking water.